Systematic Literature Review: The Role of Internal Control Systems on Sustainability Disclosure - Almira Yumna Putri; Wirmie Eka Putra; Yuliusman Yuliusman; Fredy Olimsar (International Journal of Economic and Business Research, 2026)
This study employs a bibliometric Systematic Literature Review (SLR) approach to examine the role of internal control systems in sustainability disclosure and to map the development of related research during the 2016–2025 period. The study utilized articles indexed in the Scopus database and other reputable scientific sources by applying purposive sampling techniques. A total of 20 selected articles were analyzed based on publication trends, research sectors, methodologies, and thematic focus. The findings indicate that internal control systems play a significant role in supporting corporate sustainability by enhancing transparency, accountability, reporting integrity, and governance effectiveness. Internal control has evolved from a compliance-oriented mechanism into a strategic instrument for achieving long-term sustainability goals within organizations. The review also reveals that integrating internal control systems with Environmental, Social, and Governance (ESG) strategies, corporate social responsibility (CSR), digital governance, and sustainability accounting systems contributes positively to organizational performance across financial, social, environmental, and governance dimensions. Furthermore, bibliometric mapping demonstrates a significant increase in scholarly attention to this topic, particularly during the 2022–2024 period, reflecting the growing global demand for sustainable business practices and ESG reporting. The study also identifies several research gaps, particularly the limited number of studies conducted in developing countries and the lack of research examining the influence of digital governance, organizational culture, and gender diversity on the effectiveness of internal control systems in sustainability disclosure. Overall, this study provides both theoretical and practical contributions to the development of sustainability governance and highlights future research opportunities in the field of internal control and sustainability disclosure.